Skin Cancer in Asians: Part 2: Melanoma - Bellew, Susun (Matrix Medical Communications, 2009)
The Asian population in the United States is expected to increase in the next 50 years. Concurrently, there is an overall rise in the incidence of melanoma. It is therefore crucial to obtain a better understanding of this deadly skin cancer in this minority population, as little information is currently available and prognosis remains poor. Through a review of the literature, this paper explores melanoma in the Asian population, including the most common subtype encountered, prognosis, theories on pathogenesis, and molecular biology.